Meaningful tourism : strategies and future development - Tyagi, Pankaj Kumar; Nadda, Vipin; Kumar Singh, Ajit (Building the future of tourism, 2025)
In an era marked by increasing global travel, the need for responsible and sustainable tourism practices has never been more pressing. Exploration of the vital connections between tourism, local communities, and the environment will decide the future success of the industry. Meaningful Tourism: Strategies and Future Development aims to heighten awareness about the crucial role travellers play in shaping the destinations they visit. By illuminating the far-reaching impact of individual actions, the authors outline how responsible choices now can ensure a positive legacy for generations to come. From selecting eco-friendly accommodation and engaging in sustainable activities, to championing local businesses and minimising the ecological footprint of travel, this comprehensive resource equips travellers with the tools to embrace a transformative journey. Drawing from real-world examples of successful meaningful tourism initiatives, Meaningful Tourism showcases the remarkable positive outcomes that responsible travel can bring. Witness how communities thrive, cultures flourish, and environments rejuvenate when travellers embrace their role as stewards of the places they explore.